Mapping privity of e-commerce consumer contracts for sale of goods - Ong, Tze Chin; Ow, Yong Mun Geet; Ong, Tze San (Asian Scholars Network, 2019)
E-commerce has change conventional sale of goods through global access in online marketplace. The borderless online marketplace provides a worldwide platform for sale of goods to consumers. A new group of tech-savvy consumers, also known as e-consumers emerge and growing rapidly over the years for cheaper, easy access, convenient, more varieties, quality of goods in e-commerce. E-commerce transactions on sale of goods involve many parties, among others, the platform provider, the seller (either manufacturer, intermediary, wholesaler or retailer), the internet provider, the financial service provider that provides the transfer of money using data, the website, the logistics provider, the shipping company, the delivering company and the consumers as buyer at the end of the transaction. In some circumstances, consumers can even be the seller in e-commerce. The parties to the e-commerce contract is essential to determine the rights and liabilities of the contracting parties, which raise the issue of privity of contract and other related issues on contract law. The nature and the complexity of e-commerce consumer contracts for sale of goods trigger many legal issues; form the beginning of forming of the contract to the conclusion of the contract. This paper focusing on the issue arising on the contractual rights and obligations of the e-commerce contract for sale of goods. Pure doctrinal legal research by employing content analysis method, this paper aims to draw connection among the parties direct and indirectly involved it the contract. This paper also seeks to identify and analyses the relationship of various parties involved in e-commerce consumer contracts for sale of goods. To examine and review the relationship of the parties in e-commerce sale of goods contract with regard to their rights and liabilities involved, with the aim to ascertain its’ coherent with the privity of contract doctrine.